2017
DOI: 10.21548/38-1-1038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Sunlight Intensity on the Temporal Phenolic Profiles of Vitis Vinifera L. Cv. Chardonnay During the Ripening Season – A Field Study

Abstract: Grape phenolics are considered to have a significant impact on wine quality, with their quantity and dynamics being strongly influenced by environmental conditions. We investigated the effect of ambient sunlight on the temporal dynamics of phenolics in cv. Chardonnay under field conditions during the 2012 ripening season, from véraison until harvest. The phenolic profiles of the grapes were monitored at predefined time intervals by using high-pressure liquid chromatography (HPLC) and spectrophotometric (OD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Thus, the weather and climate conditions could be the reason for the differences in phenolic levels in the wines produced in the two vintage years. Previous studies have attributed differences in the level of phenolic compounds in grapes of the same genotype grown in different years to changes in temperature, water availability (drought or precipitation), light intensity, salinity and pollination [33,34]. Our findings are in agreement with the results from previous research studies, indicating that weather conditions influence the content of stilbenes in wine [35,36].…”
Section: Resultssupporting
confidence: 92%
“…Thus, the weather and climate conditions could be the reason for the differences in phenolic levels in the wines produced in the two vintage years. Previous studies have attributed differences in the level of phenolic compounds in grapes of the same genotype grown in different years to changes in temperature, water availability (drought or precipitation), light intensity, salinity and pollination [33,34]. Our findings are in agreement with the results from previous research studies, indicating that weather conditions influence the content of stilbenes in wine [35,36].…”
Section: Resultssupporting
confidence: 92%
“…Other studies have also found significant differences between seasons (Brossaud et al, 1999; Spayd et al, 2002), whereas Mazza et al (1999) reported a minimal influence of the season in Cabernet franc, Merlot, and Pinot noir due to an atypical growing season over three seasons. Recently, Šebela et al (2017) suggested that the phenolic concentration in Chardonnay is a function of the sunlight intensities preceding the sampling date during the ripening season.…”
Section: Resultsmentioning
confidence: 99%
“…Shade changes the quality of light that reaches grapevines as well; different wavelengths of light have different effects on grapevine physiological and morphological characteristics (Krueger 1981;Šebela et al 2017). Red and blue light rays are the most photosynthetically active rays, and thus promote the most photosynthesis, while yellow and orange light promotes cell elongation.…”
Section: Iv21 the Effects Of Sun And Shade On Grapevine Physiological Parametersmentioning
confidence: 99%